If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 = 4(8x + 1) Reorder the terms: 36 = 4(1 + 8x) 36 = (1 * 4 + 8x * 4) 36 = (4 + 32x) Solving 36 = 4 + 32x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32x' to each side of the equation. 36 + -32x = 4 + 32x + -32x Combine like terms: 32x + -32x = 0 36 + -32x = 4 + 0 36 + -32x = 4 Add '-36' to each side of the equation. 36 + -36 + -32x = 4 + -36 Combine like terms: 36 + -36 = 0 0 + -32x = 4 + -36 -32x = 4 + -36 Combine like terms: 4 + -36 = -32 -32x = -32 Divide each side by '-32'. x = 1 Simplifying x = 1
| 3(w+7)=-3 | | 8(1-4x)+8(x+3)=32 | | 8(1-4x)+8(m+3)=32 | | 4(0+1)=4(x+8) | | 22+2z=52 | | 9d+1=8d-18 | | 3(g+8)-2=7 | | 6x^6-96x^2=0 | | 4x+8=15x-3x | | -4=5+3n | | 0=2(sin)x*2(cos)x | | 6-x=42 | | (2u+5v)(2u-5v)= | | -28x+24-3x-12=30 | | 104x=3x+6 | | 17/2+1/2= | | 6a+3=3a+15 | | 0=2sinx*2cosx | | 2y+7x=-5 | | 2=4r+n | | 3+17+5x=7x+10 | | 99=2d-419 | | h(1)=5 | | -x^2+9x=16 | | 6(5y-8)-(4y+7)= | | 4(-7x+6)-3(x-2)=30 | | 8t^2+64=0 | | 3-2(4n-6)=5(n+4) | | -2(n+1)=0 | | X^4+20=21 | | 69+2u=-23 | | 8x-(3x-17)=52 |